Special criminal investigation (in absentia): problematic issues of a defence counsel's participation - M. М. Kolomoitsev (Bulletin of Kharkiv National University of Internal Affairs)
Based on the analysis of the criminal procedure legislation and generalisation of theoretical developments, the article identifies some peculiarities of legal regulation of the institute of special criminal proceedings (in absentia). The author identifies the categories of cases (types of criminal offences) and procedural grounds which are sufficient to initiate a pre-trial investigation in the form of special criminal proceedings. The need to exclude certain articles from the list of those listed in part 2 of Article 297-1 of the CPC of Ukraine in order to bring them in line with the provisions of the Criminal Code of Ukraine is emphasised.